Bio-Insecticidal Nanoemulsions of Essential Oil and Lipid-Soluble Fractions of Pogostemon cablin - Manjesh, Keerthiraj; Kundu, Aditi; Dutta, Anirban; Saha, Supradip; Neelakanthaiah, Bhagyasree Sira (Frontiers in Plant Science, 2022)
The present study aimed to develop nanoemulsions (NEs) of essential oil (EO) and lipid-soluble extract (HE) of Pogostemon cablin leaves using biosurfactant, saponin. Hydro-distilled EO and fat-soluble HE were analyzed using GC-MS, which revealed 38.7 ± 2.7% and 37.5 ± 2.1% patchoulol, respectively. EO and HE were formulated with saponin to prepare corresponding coarse emulsions (CEs); furthermore, high-speed homogenization for 2 min was followed by ultrasonication for 3 min with constant frequency of 50 kHz. of the CEs resulted in respective NEs. NEs were characterized for the physico-chemical properties such as emulsion intrinsic stability, particle size distribution, polydispersity index (PDI), and transmission electron microscopy (TEM) for morphology and accurate nanodroplet diameters. CEs and NEs were investigated for insecticidal efficacy against adults of Tetranychus urticae and larvae of Spodoptera litura. Stable NEs of EO and HE at 500 μg mL−1 concentration exhibited corresponding average particle size of 51.7 and 89.9 nm, while TEM image revealed spherical-shaped droplets with the average droplet diameters of 15.3 and 29.4 nm, respectively. NEs of EO and HE displayed highest efficacy in contact toxicity (LC50 43.2 and 58.4 μg mL−1) after 48 h and fumigant toxicity (LC50 9.3 and 13.6 μg mL−1) after 24 h against T. urticae. In addition, NEs of EO showed considerable antifeedant and feeding deterrent action (AI 99.21 ± 0.74 and FI 99.73 ± 1.24) against S. litura larvae.